Pengembangan Standar Operasional Prosedur (SOP) Penggunaan Peralatan Praktik Di Bengkel Teknik Kendaraan Ringan Otomotif (TKRO) SMK Negeri 2 Depok Sleman - Dycka Sabrisirach Putra Herman; Yoga Guntur Sampurno (Journal of Automotive Technology and Education, 2026)
Abstract The development of Standard Operating Procedures (SOPs) for the use of practical equipment in the TKRO (Automotive Engineering) competency at SMK Negeri 2 Depok Sleman is the primary focus of this study. In addition, this study aims to evaluate the extent to which the developed SOPs meet feasibility standards for implementation in practical learning activities. The approach employed is the Research and Development (R&D) method using the Four-D (4D) model, which consists of the stages of define, design, develop, and disseminate. Data collection was conducted using questionnaire instruments, which were then analyzed through quantitative descriptive techniques. The product evaluation involved two types of validators, namely a material expert and a media expert. Furthermore, productive teachers, the head of the TKRO program, and 27 students were involved as users to provide assessments and feedback on the developed SOPs. The final results of the study indicate that three SOPs were successfully developed, namely a computer-based car wheel alignment (spooring) SOP, an SOP for compressor usage, and an SOP for car lift operation. Based on the validation results, the material expert awarded a score of 78 with a percentage of 98%, categorized as “very feasible.” Meanwhile, the media expert gave a score of 58 with a percentage of 73%, categorized as “feasible.” The results of the student trial showed a total score of 1,785 with a percentage of 83%, which is also considered “feasible”. Thus, the developed SOPs are deemed to have met the feasibility criteria and can be used as guidelines for conducting practical activities in the TKR workshop. Abstrak Upaya penyusunan Standar Operasional Prosedur (SOP) dalam penggunaan peralatan praktik pada Kompetensi Keahlian TKRO di SMK Negeri 2 Depok Sleman menjadi fokus utama dalam kajian ini. Selain itu, kajian ini juga diarahkan untuk menilai sejauh mana SOP yang dihasilkan memenuhi standar kelayakan untuk dipergunakan dalam kegiatan pembelajaran praktik. Pendekatan yang diterapkan ialah metode Research and Development (R&D) dengan model Four-D (4D) yang meliputi tahap pendefinisian, perancangan, pengembangan, hingga penyebarluasan. Proses pengumpulan data dilakukan melalui instrumen angket yang kemudian dianalisis menggunakan teknik deskriptif kuantitatif. Penilaian pada produk melibatkan dua jenis validator, yakni ahli materi serta ahli media. Selain itu, guru produktif, kepala program keahlian TKRO, dan 27 peserta didik turut dilibatkan sebagai pengguna untuk memberi penilaian serta masukan pada SOP yang dikembangkan. Hasil akhir penelitian memperlihatkan jika terdapat tiga SOP yang berhasil disusun, yakni SOP pengecekan spooring mobil berbasis komputer, SOP penggunaan kompresor, serta SOP penggunaan car lift. Dari hasil validasi, ahli materi memberi skor 78 dengan persentase 98% yang termasuk kategori sangat layak. Sementara itu, ahli media memberi skor 58 dengan persentase 73% yang masuk dalam kategori layak. Adapun hasil uji coba pada peserta didik memperoleh skor total 1.785 dengan persentase 83% yang juga tergolong layak.Dengan demikian, SOP yang telah dikembangkan dinilai telah memenuhi kriteria kelayakan serta dapat dipergunakan sebagai acuan dalam pelaksanaan kegiatan praktik di bengkel TKR.